Compression rheological behavior of ultrahighly filled wood flour-polyethylene composites. (15th June 2021) - Fu, Haitao; Dun, Mengyuan; Chen, Binhui; Zhou, Zhifang; Wang, Haigang; Wang, Weihong; Xie, Yanjun; Wang, Qingwen
Abstract: Ultrahighly filled wood-plactic composites (UF-WPC, filling content exceeds 70 wt%) have high additional value and superior environmental properties due to the substantial reduction in plastic consumption. Studying the flow mode and mechanism of UF-WPC melt in the production process is critical for improving production efficiency and optimizing production equipment. In this paper, the rheological properties of ultrahighly filled wood flour-polyethylene composites (UF-WFPE) under continuous deformation were investigated using a compression rheology method. The plug flow model was introduced to analyse the rheological behavior of UF-WFPE, and was modified for UF-WFPE melt. According to the poor fluidity and strong solid-like characteristics of UF-WFPE, a self-made compression rheometer was prepared to conduct the compression rheology testing. The results indicated that the unmodified plug flow model did not apply to the continuous structural changes of UF-WFPE during compression. During continuous compression, the specimens with WF content of 70 wt%, 75 wt%, and 80 wt% displayed a window period of structural stability before the edge fracture, which indicated the stable rheological behavior. However, as the WF content increased to 90 wt%, the edges of the melt entered the continuous fracture stage after the compaction stage, and no stable rheological behavior period was observed. Based on the modified plug flow model, the rheological stress formula with WF as variable was obtained by fitting rheological stresses of different systems in the steady flow stage, and the reliability of the formula was verified. This study provides an effective method for the rheological analysing of ultrahighly filled wood-plastic composites and lays a theoretical foundation for its practical production and application.